A Maine Response - Orr, James (Maine Policy Review, 1993)
The 20th anniversary of the Governor’s Economic Development Conference last October focused on the impact of public policy on the competitiveness of Maine’s business and industry. UNUM Chief Executive Officer James F. Orr III cautioned conference attendees that, while President Clinton deserves credit for some of his early initiatives, the path to establishing a national economy that will position the U.S. for the next century is a long and difficult one. Orr’s presentation was a response to the President Clinton administration’s top economic adviser, Laura D’Andrea Tyson regarding the administration’s policy initiatives meant to enhance the nation’s competitiveness relative to the international economy.
Keywords: Maine; public policy; economic development; health care reform; NAFTA